Experience of the department of pediatrics in the use of remote tools for academic continuity at the Pontificia Universidad Javeriana, during the SARS-CoV2 pandemic in 2020 (2021)
Medical education has been confronted with the rapid changes that occurred as a result of the SARS-CoV-2 pandemic. The Pediatrics Department of the Faculty of Medicine of the Pontificia Universidad Javeriana have faced the need of modifications and have e